The use of Jclic as complement for the teaching/learning of the Phisical Education - Antonio Ariza García; Santiago Romero Granados (FEADEF, 2009)
In this article we seek to show the importance of the program Jclic in the design of applications didactic multimedia and interactive that procedural aspects of diverse areas of the curriculum work that embrace from the infantile education until the secondary education. In particular, we will center ourselves in the design of activities for the introduction from the Physical Education to different levels.